Wudhu Sebagai Upaya Pencegahan Penularan Covid-19 (Dusun Sambong Desa Sumberkepuh Kecamatan Tanjunganom) - Nurmahmudah; As-Syury, Muhammad Barozan (Spiritualita, 2020)
Covid-19 is a virus that has spread and is troubling mankind. Its spread is so fast that every country makes efforts to handle and prevent the spread of covid-19. As one of the efforts to prevent Covid-19 is implementing health protocols, one of which is washing hands with soap and ablution are very important teachings and are a legal requirement for praying, besides being harmonious and sunna, ablution also provides health benefits and also eliminates viruses attached to the body like the covid-19 virus. This methodology uses descriptive qualitative methods, which are methods for obtaining information and descriptions of phenomena or events that occur. This study uses a premiere data source. Supported by secondary data sources in the form of scientific references such as books, scientific journals, online news and interviews. Data collection techniques used direct observation, non-formal interviews, and literature searches. The observation method used was non-systematic and non-participant methods. Libraries are obtained through scientific journals, books and the internet.